Analisis Kompetensi Profesional Guru Sekolah Dasar - Wilson Takaendengan; Indriani Julefta Maradesa; Bertu Rianto Takaendengan (Departement of Mathematics Education, 2023)
This study aims to obtain a description of the professional competence of teachers at SD Katolik V Santo Agustinus Tomohon. This research is a form of qualitative descriptive research with data sources coming from the principal and several classroom teachers. Data collection techniques used include interviews, observation, document analysis. The analysis technique includes data reduction, data presentation, making conclusions or verification, while the data validity test uses source triangulation techniques and technical triangulation techniques. The results of this study indicate that the professional competence of teachers at SD Katolik V Santo Agustinus Tomohon can be categorized as quite good when viewed from the following aspects: 1) mastery of learning materials; 2) the ability to develop the profession; 3) understanding of insight and educational foundation.